Enhancing English Vocabulary Mastery Through Flashcards: A Study on Fifth Graders at SDN 05 Palembang - Novasyari, Ressy (Journal of Education Research, 2024)
This study examines the effectiveness of flashcards in improving English vocabulary mastery among fifth-grade students at SDN 05 Palembang. Using a qualitative descriptive approach and questionnaires as data collection tools, the study revealed that 85% of students found flashcards helpful in understanding English vocabulary. The research concludes that flashcards are an effective and interactive tool for enhancing vocabulary mastery and creating an engaging learning environment.